Confronting total systemic failure? The May 2018 truckers' strike in Brazil. (8th July 2019) - Schlindwein, Sandro Luis; Ison, Ray
Abstract: In May 2018, truckers in Brazil went on strike for 10 days to protest against rising diesel prices and for better freight payments. The strike caused an unprecedented level of disruption in many supply‐and‐distribution networks affecting almost all sectors of the economy and the society. Using causal loop diagrams (CLDs) within a systemic‐inquiry approach, an analysis of the circumstances that led to the strike and the resulting systemic failures is developed. Although the main driver of the strike was the fuel‐price policy of Petrobras, a semi‐public Brazilian corporation in the petroleum industry, the level of the observed disruption was primarily the result of a cascade of failures in a range of coupled systems. From the circumstances that led to the strike and its disruptive effects, lessons for future policy are reported making evident the need for transformative governance arrangements, particularly innovative governance practices to prevent failure and disruption in highly interconnected systems.